Determinants of accounting students’ performance in MUET examination / Noorain Omar...[et al.] - Omar, Noorain; Junos, Sutina; Saad, Sharina; Mohd Saad, Sazilah; Mohammed, Syakirah (Universiti Teknologi MARA, Kedah, 2013)
The use of standardised English proficiency tests like IELTS and TOEFL for admission and placement purposes is widely practised in academic institutions throughout the world. Similarly, in Malaysia many tertiary institutions utilise the results of a localised version of such tests called the Malaysian University English Test (MUET) as a measure of students’ proficiency level, prerequisite for admission, as well as placement in various academic programmes. The purpose of this conceptual paper is to investigate factors that may influence the students’ performance in MUET examination. The MUET bands of undergraduates from Faculty of Accountancy of UiTM Kedah for the year 2011 and year 2012 shall be analysed and consequently several recommendations shall be offered to improve student performance.